Impact of copper stress in the intestinal barriers and gut microbiota of Chinese stripe-necked turtle (Mauremys sinensis) - Zeeshan Ali; Ijaz Khan; Muhammad Shahid Iqbal; Haitao Shi; Li Ding; Meiling Hong (Ecotoxicology and Environmental Safety)
Copper is used to treat algal blooms, macrophyte infestations and other environmental issues, but its rising ambient levels harm aquatic animals, especially their intestines. However, its impact on turtles' digestive health is not well understood, and the risks are unclear. This study investigates the effects of copper on the intestinal health of Chinese stripe-necked turtle, focusing on histomorphology, mucosal barrier function, gene expression, and gut microbiota. Copper stress caused intestinal damage, characterized by shortened villi, inflammatory cell infiltration, and reduced epithelial layer thickness, as well as decreased acidic mucins, increased villi edema and inflammation. The mRNA expression level of bacteriostatic enzymes significantly reduced. Furthermore, This study found that copper exposure increases gut permeability by suppressing tight junction genes and triggers an inflammatory response in the gut, as indicated by elevated inflammatory cytokines. At the phylum level, Firmicutes exhibited a significant decrease, whereas Bacteroidota displayed a notable increase, and Fusobacteriota showed a substantial reduction in relative abundance in copper-treated groups. Similarly, at genus level Romboutsia, Cetobacterium decreased, while Turicibacter and Sarcina significantly increases in copper-treated groups compared to the control. This indicating the unique properties of copper including its essentiality, reactivity, and accumulation enables it to profoundly impact gut bacteria, altering both their composition and function. Copper's dual role as a nutrient and toxicant uniquely impacts gut microbes. Our findings suggest that copper stress compromises the intestinal physical, immune, chemical, and microbial barrier in M. sinensis, all of which contribute to the turtle’s poor health.